(untitled) - McCoy, Donald R. (Lawrence, Kan, 1984)
The aim of the american presidency of Harry S. Truman is personality, the fair deal, the iron curtain descends
Keywords: Tổng thống,Presidents; Tiểu sử,Biography; Hoa Kỳ,United States